Relative bioavailability of copper and molybdernum sources and effect of molybdenum on molybdnum and copper excretation and tissue accumulation in lambs. - POTT, E. B. (1992)
Five experiments were conducted, including three to estimate relative bioavailability value (RBV, :) of Cu ir sources, one to determine effects of feeding duration anc added dietary concentrations (ADC) of Mo on daily Mo (MOI and Cu excretion (CUEX) and tissue uptake, and one to estimate RBV of Mo in inorganic sources, for lambs fed a corn-soybean meal-cottonseed hulls basal diet (DIET). Fi to six lambs were assigned randomly to DIET or DIET supplemented for 10 days with 60, 120 or 180 ppm Cu as cupric chloride or 120 ppm Cu from cupric carbonate, cup oxide or cupric sulfate (Exp. 1); or 60, 120 or 180 ppm as chloride or 120 ppm Cu from cupric acetate, oxide or sulfate (Exp. 2); or 60, 120 or 180 ppm Cu as Cu-lysine sulfate (Exp. 3); or with 0, 15, 30 or 45 ppm Mo from sc molybdate (SODIUM) for 14 or 28 days (Exp. 4); or with 15.30 or 45 ppm Mo as SODIUM or 30 ppm Mo from ammonium molybdate, molybdenum trioxide or Mo metal for 28 days.